Ballot Reform and the Decline of Third Parties in State Legislatures. Issue 2 (2nd July 2016) - Reed, Daniel C.
Abstract : While it has been suggested that the original Australian ballot reforms of the late nineteenth and early twentieth centuries may have had a detrimental effect on later third-party success in US elections, others have observed that many ballot laws 'explain very little of the variance in either the number of minor party candidacies or the vote for them'. While there is much debate about the effects of these laws on electoral outcomes, a limitation of past research is an emphasis on statewide and federal elections, where many third-party candidacies are 'agenda-setting' rather than 'office-seeking' efforts. This research examines the effects of the original Australian ballot laws on state legislative elections, where office-seeking third-party candidates had a proven record of electoral success. The effects of initial reform adoption, straight ticket provisions, ballot form, prohibitions against ballot fusion, and the inclusion of write-in options on the ballot are tested in time-series Tobit models of the percentage of state house seats won by third-party candidates from 1870 to 1920. The results of the analysis suggest that the specific provisions included in these ballot laws had a statistically significant and substantial effect on later third-party success in state legislative elections.